Kajian Mengenai Kurangnya Fasilitas Perdagangan Tekstil Di Surabaya Menjadi Masalah Bagi Para Pelaku IKM - Rafif, Arya Elfreda; Rahmatullah Masruchin, Febby (Jurnal Etnik: Ekonomi-Teknik, 2024)
The aim of this research is to create a building design for the clothing industry from micro to macro level. The research method used is a case study, the paradigm used is based on facts that occur in the field and problems that exist within the scope of domestic industry. The lack of supporting capacity for industries such as textile trade makes it difficult for industrial players to obtain raw materials for production. Therefore, clothing industry players have to get the materials they need further than expected. In fact, currently several entrepreneurs have to source raw materials in the West Java area, because West Java is considered a more complete textile city for goods needed for production. Needs analysis produces building plans which are then implemented so that they can support the industrial community. The calculation results show that the construction of textile trade facilities in Surabaya has made a huge contribution to the clothing industry in the Surabaya region and even eastern Indonesia.